Knowledge, Attitude and Behavior of Consumers on Food Safety in Sri Lanka - Jayasekara, J.M.D.S.; Madhujith, W.M.T.; Panoshan, S.L. (University of Jaffna, 2022)
Food safety is very crucial in among the particular group of people. Poor eating habits are a major concern among university students. Prime objective of this research was to assess knowledge, attitude and behavior on food safety among the consumers in Sri Lanka. As the method of the research, descriptive cross sectional community based study was adopted. For the sampling it was obtain from density of the population of each district in Sri Lanka. Simple random sampling technique was employed to the study as in every district 5% of samples were collected from persons per square kilometer of each district. Samples (n = 576) were collected from each district in the Sri Lanka for the fulfillment of the survey. Finally 608 of samples were collected including 32 of volunteer people. Data were approached from person with a print version of the survey or an electronic link (Google form). A self-administered questionnaire was use consumer in this study. The Statistical Package (SPSS 20) was used for analyze the data on demographic, knowledge and attitude on food Safety parts. Through descriptive, socio-demographic and knowledge of the participants were described and expressed as frequencies. As the correlations the nutritional knowledge had significant relationship (p <0.05) and (p <0.01) as variables. According to the research hypothesis consumer knowledge, attitude and behavior on food safety differ with the gender, educational level and the occupational variables. However, geographical background of the respondents was not differing with the consumer knowledge, attitude and behavior on food safety. Behavior and food handling practices are very poor in Sri Lankan people. Therefore, the study concluded that knowledge, attitude and behavior on food safety of consumer are a critical factor that requires close attention.
Keywords: Consumer preferences; Eating habits; Food hygiene; Food safety